Penggunaan Injeksi Antibiotika Untuk Pencapaian Efek Terapi Optimal pada Pasien di Bangsal Anak - Vera, Yulia; Antoni, Adi (Universitas Aufa Royhan, 2019)
Antibiotics are substances produced by a microbe, especially fungi, which can inhibit or be able to eradicate other types of microbes. The main therapy for infection is antibiotics. Health problems in children will affect their growth and the possibility of children being hospitalized is very high. Pediatrics have rudimentary organ metabolism, cannot receive the same treatment as adults. Drug therapy for children needs perfect management, ranging from diagnosis, drug selection, dosage, to monitoring drug use. Examples of inappropriate use of antibiotics include treatment of infections that are not responsive, fever therapy with no known cause, incorrect dosage, improper use of a single antibiotic, inadequate bacteriological information in its use. The preparation and storage of antibiotics must be in accordance with pharmaceutical requirements in the finished preparations as well as after reconstitution. Preparation and storage of antibiotics according to standards is intended to ensure the quality of preparations when used by patients. The selection of solvents must pay attention to compatibility, for example: ceftriaxone is not compatible with solvents / solutions containing calcium. Based on the description above, the researcher feels it is important to conduct studies on the use of antibiotic injections to achieve optimal therapeutic effects in patients at RS X. research conducted on studies to achieve optimal therapeutic effects in the Children's Ward RS X. longitudinally during April 2013 to July 2013. The most widely used antibiotics are gentamicin.